GRAND DESIGN OF EDUCATIONAL INSTITUTIONS IN CHARACTER EDUCATION (An analysis of problems and New Formulations, in the approach to character education) - Reksiana, Reksiana (al-Iltizam: Jurnal Pendidikan Agama Islam, 2019)
the existence of differences of view to education children character, and can be classified in several categories and theories. This difference is seen as some figures say families or tualah people are the most important in providing character education. Others argue sekolahlah that is most vital in respect of containers of character education. This article uses a qualitative approach, with the kind of Library Research. Therefore, the overall data focuses on books or papers relating to discussion of "rightmost character Education". Quant à la méthode d’analyse de données technique utilisée est descriptive analyse qualitative méthodes, car les données sont traitées sous la forme d’un écrit de données telles que : livres, revues, articles de journaux, caractère education curriculum directives structures formelles en 2013 en ligne En ligne) et comprend le produit brut standard sous forme de législation relative à la formation du caractère. From the results of the discussion and anlisa above, concrete conclusions can be taken, that the person in charge character education namely Educational Institutions not the independence of each other, but rather inherently. Summary this rests on a concrete analysis of the various figures such as: Thomas Lickona, Jun Sung Hong and James Garbarino, David w. Johnson, and Roger t. Johnson, even from muslim figures like Abdul Majid, Jamal ‘Abdur Rahman, Moh. Solikodin Djaelani, Muchlas Samani dan Abdullah Nashih ‘Ulwan, first product reinforced by legislation which clearly explains the RI character education is the shared responsibility of educational institutions.